SERS Spectroscopic and electrochemical insights into Methyl Parathion reactivity on gold surface - Yamanaka, Ana Luiza Clivatti; Rangel, Clara de Jesus; Ando, Rômulo Augusto (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2025)
[Display omitted] •Surface-enhanced Raman spectroscopy (SERS) was used to investigate methyl parathion reactivity on gold surfaces.•The degradation product p-nitrophenol undergoes further dimerization via azo bond formation.•Spectroeletrochemical measurements confirm the coexistence of multiple surface-bound species.•Findings help explain the high variability in MP SERS spectra reported in previous studies. Surface Enhanced Raman Scattering (SERS) has been widely explored for detecting trace amounts of pesticides in food due to its high sensitivity, which is crucial for monitoring the illegal use of these substances. While various studies have reported SERS-based strategies for detecting Methyl Parathion (MP), a banned insecticide, there remains a lack of detailed investigation into the spectral features linked to potential chemical reactions occurring upon MP adsorption on metallic surfaces. This gap in understanding contributes to significant variance in the reported SERS signals, compromising the reliability of analytical methods. In this work, we demonstrate that MP is cleaved upon adsorption onto gold nanostructured surfaces, with p-nitrophenol residue undergoing further dimerization via plasmonic catalysis process, forming an azo bond under specific experimental conditions. SERS spectra obtained with 785 nm excitation show a pronounced band at ca. 1330 cm−1, assigned to the symmetric stretching of the nitro group, νs(NO2), from p-nitrophenol species. When the SERS spectra is obtained with 633 nm excitation, azo bond vibrations, ν(N=N), at ca. 1410 and 1460 cm−1, are more prominent indicating the dimerization of p-nitrophenol fragments. Additionally, electrochemical SERS analysis revealed potential-dependent molecular transformations, including energy modulation of the photochemical reaction process, reaching optimal dimerization occurring around –0.2 V. Further reduction at approximately –0.6 V led to the formation of p-aminophenol from the p-nitrophenol fragment. These findings highlight the complexity of surface-mediated processes, underscoring the need for thorough investigation to develop robust and reproducible SERS methodologies for pesticide and pollutant detection.